Persaingan Usaha Jasa Transportasi Online Ditinjau Dari Undang-Undang Nomor 5 Tahun 1999 (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
In the current era of globalization, the progress of technology and information development occurs very quickly. Developments in the transportation sector have experienced significant changes with the presence of online transportation services in the form of an application. Online transportation service applications are very easy to use which has an impact on other transportation services. Therefore, the purpose of this discussion is carried out in order to find out how business competition lies therein, including between online transportation service business actors and ordinary (conventional) transportation businesses. Some online transportation service providers in Indonesia include Uber, Grab, Go-jek, In-driver, and others. The services provided by online transportation services are not only in the form of transportation services, but offer food delivery services, online shopping services, and services to deliver packages. Business competition between online transportation services and (conventional) transportation services causes unfair business competition. In this research, the author uses a qualitative research type because the author discusses the business competition between the two by conducting an analysis. The research approach used by the author in this journal is to use a statutory approach.